Innovation Strategy Role in Tourists Visit Improvement. Context of Man-Made Tourism in Indonesia - MUAFI, MUAFI; WIJAYA, Taufiq; DIHARTO, Awan Kostrad; PANUNTUN, Bagus (Journal of Environmental Management and Tourism, 2018)
The study aims to analyze the innovation strategy impact on improvement of man-made tourist visit in Indonesia. Nowadays, man-made tourism is very popular for society as an alternative family tourism for entertainment, education and refreshing. The type of study uses a qualitative approach. Data collection techniques are conducted by in-depth interviews with man-made tourism actors in Indonesia, especially at Jatim Park Batu Malang, East Java Province, Taman Mini Indonesia Indah, Jakarta Province, Ragunan Zoo, Jakarta Province and Ancol, Jakarta Province, Indonesia. The researcher team also conducted data collection through photographs and records in the field. The study result recommends that man-made tourism requires innovative, effective, efficient and not easily imitated innovation strategies to increase the number of tourists so they can compete with other tourism such as natural and cultural tourism. Man-made tourism business actors need to manage well and professionally so the man-made tourism visitors will increase in the long term.